Growth and thermal stability of TiN/ZrAlN: Effect of internal interfaces. (December 2016) - Yalamanchili, Kumar; Wang, Fei; Aboulfadl, Hisham; Barrirero, Jenifer; Rogström, Lina; Jiménez-Pique, Emilio; Mücklich, Frank; Tasnadi, Ferenc; Odén, Magnus; Ghafoor, Naureen
Abstract: Wear resistant hard films comprised of cubic transition metal nitride (c-TMN) and metastable c-AlN with coherent interfaces have a confined operating envelope governed by the limited thermal stability of metastable phases. However, equilibrium phases (c-TMN and wurtzite(w)-AlN) forming semicoherent interfaces during film growth offer higher thermal stability. We demonstrate this concept for a model multilayer system with TiN and ZrAlN layers where the latter is a nanocomposite of ZrN- and AlN- rich domains. The interfaces between the domains are tuned by changing the AlN crystal structure by varying the multilayer architecture and growth temperature. The interface energy minimization at higher growth temperature leads to formation of semicoherent interfaces between w-AlN and c-TMN during growth of 15 nm thin layers. Ab initio calculations predict higher thermodynamic stability of semicoherent interfaces between c-TMN and w-AlN than isostructural coherent interfaces between c-TMN and c-AlN. The combination of a stable interface structure and confinement of w-AlN to nm-sized domains by its low solubility in c-TMN in a multilayer, results in films with a stable hardness of 34 GPa even after annealing at 1150 °C. Graphical abstract: